Container logistics : the role of the container in the supply chain. (KoganPage, 2018)
Whilst the maritime container business has been studied in depth, the impact on shippers and how shippers deal with the given challenges has not been fully examined. Container Logistics bridges this gap and looks at the maritime business from a customer's perspective. The book examines the challenges, solutions and the latest developments in the container industry as well as the interaction between the different actors involved, such as freight forwarders, supply chain managers and shippers. Current hot topics from the supply chain and the maritime business perspective are included.From the supply chain perspective, Container Logistics covers areas such as the purchase of transportation services from ocean carriers and transport management, to effective and efficient logistics execution. From the maritime business perspective, the book covers topics such as intermodal freight optimisation and hinterland transportation, and terminal and port optimisation. With the inclusion of clear examples of best practice and bona fide case studies, as well as invaluable contributions from an international team of experts, Container Logistics is an essential guide for supply chain managers and shippers, as well as academics and industry professionals working in the maritime business. Online supporting resources include images from the book and chapter summaries.- Resumé vydavatel
Keywords: kontejnerová přeprava; přeprava zboží; logistika (management); container transportation; goods transportation; business logistics; electronic books; papers of several authors; sborníky; elektronické knihy